Perajin Sedotan Purun Di Sungai Sebangau: Produk Ramah Lingkungan Berbahan Baku Lokal: Purun Straws Craftsman on the Sebangau River: Eco-Friendly Products from Local Raw Materials - Yosefin Ari Silvianingsih; Eva Oktoberyani Christy; Nursiah Nursiah; Mahdi Santoso (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
The problem of plastic waste is still an environmental threat, but efforts to suppress plastic waste continue to be developed until now. Purun straws are a biodegradable product to solve the problem of plastic waste. So, purun straw products can become the concern of an environmentally aware global community. The research aims to describe purun straws as an eco-friendly product. In-depth interviews with key informants revealed that purun danau (Lepironia articulate) was sufficiently available as a raw material, and a semi-finished purun straw product was produced, which was eco-friendly